Efectos de la Puesta en Marcha de la Empresa Mieles S.A.S (2018)
In this article we analyze the results of the research Analysis of the effects Derived from the Start-up in March of the Company Mieles SAS, which aims to be the subject of the technical, economic, administrative and sociocultural services of the start-up of the company Mieles SAS, In the interest groups analyzed.The commercial purpose of the company is to offer the maquila service of panela in the Hoya del Río Suárez, having as tools the machinery and services that are used for a large scale, with the highest levels of effectiveness and efficiency than those of a artesanal trapiche, offering stable prices to the sugarcane growers and expanding the possibilities of commercialization, establishing formal conditions for the workers and propitiating spaces of qualification to the beneficiary cañicultores.The research is based on this article, is supported  by across-sectional descriptive study, where the instruments have focused on the interview addressed to the general manager and to the interest groups studied.With the results obtained in the investigation it was evidenced that the start-up of Mieles S.A.S., has promoted the feminine work, the arrival of qualified personnel, and the formalization of employment in the region. Likewise, the company can establish strategies that leverage the interest groups studied.